Dualistic roles and management of non-cultivated plants in lowland rice systems of East Africa - Makokha, D.W.; Irakiza, R.; Malombe, I.; Le Bourgeois, T.; Rodenburg, J. (Elsevier, 2017)
An ethnobotanical study in lowland rice areas in East Africa was undertaken to assess farmers' knowledge on the usage of non-cultivated plants occurring in paddy fields, and to understand what rice farmers in this region do with useful species once they encounter them in their crop. Inventories of weed species in 19 rice schemes in Tanzania and Kenya were followed by interviews among 380 experienced rice farmers, community elders and traditional healers, grouped into 19 informant groups. Among informant groups, a high degree of consensus about uses of weeds growing in rice paddies was observed. From a total of 222 observed rice weed species, the informant groups identified 67 species with usages described in 1300 use reports. Among these 67 species, 20 are among the most commonly cited weed species in rice paddies in sub-Saharan Africa. Only in 42 cases (3% of the total use reports) did the farmers indicate that they collected (13 species) or spared (four species) these weeds during weeding. In all other cases, such plants were removed or killed during weeding, irrespective of their usefulness. Non-cultivated plants that are spared are those of which the putative agronomic qualities (i.e. for crop protection or soil improvement) are considered more important than their crop competition effects (i.e. Azolla filiculoides and Marsilea crenata) and those that are found in the field margins, which do not compete with the crop. Non-cultivated plants that are collected during weeding have food, fodder or medicinal purposes or a combination of purposes. The most cited species that are collected or spared during weeding were Bidens pilosa, Ipomoea aquatica, Corchorus olitorius and Stachytarpheta jamaicensis. This study revealed that lowland rice farmers in East Africa generally have a high level of understanding and consensus on the usefulness of the non-cultivated plants growing in lowland rice schemes. When they occur in their crop however, the vast majority of these species are primarily seen as weeds and consequently removed or killed.